Clinical Implications of the Lung Ultrasound Score in Patients after Cardiopulmonary Resuscitation - Zhang, Yi-Ling; Yang, Zhou; Cao, Jie; Bai, Yu-Long; Fang, Chun-Yun; Wang, Wei (Emergency Medicine International, 2023)
Background. Lung ultrasound score (LUS) is a clinical index used to measure lung injury, but its clinical value in patients after cardiopulmonary resuscitation (CPR) remains relatively unknown. The purpose of this study was to investigate the clinical value of LUS in patients after CPR. Methods. This retrospective study included a total of 34 patients older than 18 years with a nontraumatic cause of in-hospital cardiac arrest, who received standard resuscitation and achieved return of spontaneous circulation (ROSC). All patients underwent bedside lung ultrasound examination within half an hour once ROSC was achieved, and LUSs were calculated. The study included patient death as the endpoint event. Results. Compared with the group with lower LUSs, the patients with higher LUSs had a lower oxygenation index, longer duration of CPR, and lower 72 h survival rate. The initial LUS had good clinical value in predicting the secondary outcomes of CPR (adjusted odds ratio (aOR): 1.353, 95% confidence interval (CI): 1.018–1.797, and P = 0.037) and 72 h survival rate of patients who underwent CPR (aOR: 1.145, 95% CI: 1.014–1.294, and P = 0.029). Conclusions. LUS was shown to be helpful and had a prognostic value in patients after CPR.